No socioeconomic inequalities in mortality among Catholic monks: a quasi-experiment providing evidence for the fundamental cause theory - Schmitz, Alina; Lazarevic, Patrick; Luy, Marc (Technische Universität Dortmund, 2024)
We propose a novel approach to test the fundamental cause theory (FCT) by analyzing the association between socioeconomic status (SES), as measured by the order titles “brothers” and “padres,” and mortality in 2,421 German Catholic monks born between 1840 and 1959. This quasi-experiment allows us to study the effect of SES on mortality in a population with largely standardized living conditions. Mortality analyses based on Kaplan-Meier product limit estimation show that there were no statistically significant survival differences between the high and lower SES monks. This holds for all birth cohorts, indicating that monastic life offers health protection for monks with a lower SES regardless the disease patterns, causes of death, or main risk factors in a given period. These findings support the FCT: Whereas SES-related differences in mortality are a widely confirmed finding in the general population, a context with largely standardized conditions eliminates the importance of SES-related resources.
Journal of health and social behavior
Keywords: Cloister study; Health inequalities; Mortality; Religious communities; Socioeconomic status; 300; Kloster; Sterblichkeit; Gesundheit